2017
DOI: 10.1186/s12955-017-0725-6
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity, resilience and health-related quality of life in Chinese patients with rheumatoid arthritis: a multi-center, cross-sectional study

Abstract: BackgroundPositive psychological constructs that can moderate or mediate the negative impact of disease activity on health-related quality of life (HRQOL) in patients with rheumatoid arthritis (RA) have not been explored widely. This study aimed to assess the associations of disease activity, resilience with HRQOL and the moderating and mediating roles of resilience among Chinese RA patients.MethodsA multi-center, cross-sectional study was conducted in RA inpatients in northeast of China. A total 298 subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 48 publications
(83 reference statements)
5
43
0
3
Order By: Relevance
“…The patient narratives in our study suggest that the development of resilience promotes psychological well-being as well as self-care behaviors, such as adherence to physical therapy/ exercise routines or managing one's medical information. This finding is consistent with previous literature suggesting that resilience benefits patients with rheumatic diseases through improved physical and psychological functioning (24,28), lower fatigue (40) and disease activity, and higher mental health-related quality of life (27).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The patient narratives in our study suggest that the development of resilience promotes psychological well-being as well as self-care behaviors, such as adherence to physical therapy/ exercise routines or managing one's medical information. This finding is consistent with previous literature suggesting that resilience benefits patients with rheumatic diseases through improved physical and psychological functioning (24,28), lower fatigue (40) and disease activity, and higher mental health-related quality of life (27).…”
Section: Discussionsupporting
confidence: 93%
“…Among RA patients, high resilient coping tempered the association of pain symptoms and stress with depressive symptoms (20). Resilience is negatively associated with fatigue (26) and is thought to protect against the negative effects of illness-related stressors on the severity of symptoms, physical functioning, and mental health-related quality of life in RA (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of our study showed that patients with a college education or higher had a higher QoL score, which echoed the findings of Liu's study [32]. On the one hand, higher education levels were proven to be positively related to high resilience [33], and resilient patients are always considered to possess stronger abilities to rebound from frustration and tragedy [34].…”
Section: Discussionsupporting
confidence: 86%
“…Die aus der Erfahrungsmedizin erwachsenen konservativen Therapien hingegen finden nur selten den Weg ins Bewusstsein der Bevölkerung. Auch die Hilfe zur Selbsthilfe, wie die Diätberatung, Suchtberatung und die Beratung hinsichtlich sportlicher Belastungen sowie beruflicher und Freizeitaktivitäten stellt einen zentralen, wenn auch häufig vernachlässigten Punkt zur Verbesserung der Lebensqualität dar (3)(4)(5)(6)(7)(8).…”
Section: Discussionunclassified